Physiological Perspectives on the Use of Triheptanoin as Anaplerotic Therapy for Long Chain Fatty Acid Oxidation Disorders - Sklirou, Evgenia; Alodaib, Ahmad N.; Dobrowolski, Steven F.; Mohsen, Al-Walid A.; Vockley, Jerry (Frontiers in Genetics, 2021)
Inborn errors of mitochondrial fatty acid oxidation (FAO) comprise the most common group of disorders identified through expanded newborn screening mandated in all 50 states in the US, affecting 1:10,000 newborns. While some of the morbidity in FAO disorders (FAODs) can be reduced if identified through screening, a significant gap remains between the ability to diagnose these disorders and the ability to treat them. At least 25 enzymes and specific transport proteins are responsible for carrying out the steps of mitochondrial fatty acid metabolism, with at least 22 associated genetic disorders. Common symptoms in long chain FAODs (LC-FAODs) in the first week of life include cardiac arrhythmias, hypoglycemia, and sudden death. Symptoms later in infancy and early childhood may relate to the liver or cardiac or skeletal muscle dysfunction, and include fasting or stress-related hypoketotic hypoglycemia or Reye-like syndrome, conduction abnormalities, arrhythmias, dilated or hypertrophic cardiomyopathy, and muscle weakness or fasting- and exercise-induced rhabdomyolysis. In adolescent or adult-onset disease, muscular symptoms, including rhabdomyolysis, and cardiomyopathy predominate. Unfortunately, progress in developing better therapeutic strategies has been slow and incremental. Supplementation with medium chain triglyceride (MCT; most often a mixture of C8-12 fatty acids containing triglycerides) oil provides a fat source that can be utilized by patients with long chain defects, but does not eliminate symptoms. Three mitochondrial metabolic pathways are required for efficient energy production in eukaryotic cells: oxidative phosphorylation (OXPHOS), FAO, and the tricarboxylic (TCA) cycle, also called the Krebs cycle. Cell and mouse studies have identified a deficiency in TCA cycle intermediates in LC-FAODs, thought to be due to a depletion of odd chain carbon compounds in patients treated with a predominantly MCT fat source. Triheptanoin (triheptanoylglycerol; UX007, Ultragenyx Pharmaceuticals) is chemically composed of three heptanoate (seven carbon fatty acid) molecules linked to glycerol through ester bonds that has the potential to replete TCA cycle intermediates through production of both acetyl-CoA and propionyl-CoA through medium chain FAO. Compassionate use, retrospective, and recently completed prospective studies demonstrate significant reduction of hypoglycemic events and improved cardiac function in LC-FAOD patients, but a less dramatic effect on muscle symptoms.